The psychology of criminal justice - Stephenson, Geoffrey Michael (Oxford, England Blackwell, 1992)
"...integrates aspects of psychology's contributions to criminology and to socio-legal studies within a single narrative framework. It does this by describing the interpersonal and group dynamics of decision-making at key stages in the processing of accused persons from the time an alleged is committed to the moment sentence is passed.
Who is the criminal? -- Are criminals morally immature? -- Preparedness for crime -- Calculating criminal behavior -- Criminal-victim interaction -- Social psychology of criminal liability -- Police on crime -- Stories in court -- Testifying in court -- Twelve available people: how juries decide -- Punishing the offender: sentencing in practice -- Procedure and the distribution of criminal justice.
Includes bibliographical references (pages [244]-273) and indexes.
Keywords: Criminal psychology; Criminal justice, Administration of; Criminal justice personnel